Respuesta :

[tex] \begin{cases} \\ \large\bf{\green{ \implies}} \tt \: - \: \frac{1}{2} \: m \: = \: - 9 \\ \\ \large\bf{\green{ \implies}} \tt \: - \frac{1 \: m}{2} \: = \: - 9 \\ \\ \large\bf{\green{ \implies}} \tt \: - 1m \: = \: - 9 \: \times \: 2 \\ \\ \large\bf{\green{ \implies}} \tt \: - 1m \: = \: - 18 \\ \\ \large\bf{\green{ \implies}} \tt \: m \: = \: \frac{ \cancel- 18}{ \cancel - 1} \\ \\ \large\bf{\green{ \implies}} \tt \: m \: = \: \frac{18}{1} \\ \\ \large\bf{\green{ \implies}} \tt \: m \: = \: 18 \: \\ \end{cases}[/tex]